Mapping the Injury History of Indonesian Kabaddi Athletes - Irana Mery Alviana; S Sugiharto; Nia Sri Ramania; Muhamad Fahmi Hasan (Universitas Pendidikan Indonesia, 2023)
Sports injuries in athletes will affect their performance. The purpose of this study was to determine and find out the common injuries experienced by Kabaddi athletes in Indonesia. This study used a quantitative descriptive research design. The instrument used in this study was an injury report questionnaire. The questions focused on anthropometry, types of injury, and causes of injury. The population of this study was Kabaddi athletes spread across provinces in Indonesia. The samples of this study were taken using a purposive sampling technique. The inclusive criterion included Kabaddi athletes who had or were currently experiencing injuries. The samples of the study were 41 athletes (n = 41). In female Kabaddi athletes, the most common injuries were found in the upper body and experienced by athletes in the defender position (61.5%). Injuries to the lower body were mostly experienced by a raider (38.5%). The body parts that were commonly injured in male Kabaddi athletes, especially to the upper body, involved mostly wrist injuries (14.29%) followed by shoulder/clavicle and upper arm injuries (7.14%). In the lower body, the most common injuries were on the knees (21.43%) and ankles (17.86%). Meanwhile, in other parts of the body, the injury mostly occurred on the head, such as the face, nose, and mouth, (10.71%). In female Kabaddi athletes, the most common injuries occurred to the upper body, including to the shoulder/clavicle (30.77%). Meanwhile, in the lower body, the injury mostly occurred to the ankle (15.38%). This study shows that the most common injuries to male Kabaddi athletes in Indonesia are injuries to the lower body, namely the knee, and ankle, while the most common injury to female Kabaddi athletes is an injury to the upper body, namely the shoulder/clavicle.